2014
DOI: 10.3109/08923973.2014.945127
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of epidermal growth factor receptor (EGFR) monoclonal antibody and induction of growth-inhibitory polyclonal antibodies by vaccination with EGFR mimotope

Abstract: One of the proposed approaches in cancer therapy is to induce and direct the patient's own immune system against cancer cells. In this study, we determined the epitope mapping of the rat anti-human epidermal growth factor receptor (EGFR) monoclonal antibody ICR-62 using a phage display of random peptide library and identified a 12 amino acids peptide, which was recognized as a mimotope. The peptide was synthesized and conjugated to bovine serum albumin (BSA) as carrier protein (P-BSA). We have shown that ICR-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…These experiments were followed by animal immunization using peptide-BSA conjugate which confirmed cross-reactivity with EGFR of the anti-mimotope antibodies. The produced antibodies also exerted growth inhibitory effects on EGFR expressing cell line 16 .…”
Section: Introductionmentioning
confidence: 99%
“…These experiments were followed by animal immunization using peptide-BSA conjugate which confirmed cross-reactivity with EGFR of the anti-mimotope antibodies. The produced antibodies also exerted growth inhibitory effects on EGFR expressing cell line 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Peptide vaccination for cancer is one of the most main procedures in this field. Lots of peptides have been introduced as cancer vaccine like EGFR mimotope 14 , extra cellular domain of EGFR 12 , chemically synthesized peptide 17 and so on. In this study, we considered in silico construction of a new fusion peptide consisted of EGFR mimotope and L2 domain of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity against the antibodies showed that EM-L2 peptide could be a suitable candidate for EGFR-positive tumors. Moreover, Navari et al evaluated the EGFR mimotope/ICR62 reaction 14 . Our findings confirmed the EM-L2 affinity toward anti EGFR antibodies.…”
Section: Evaluation Of L2d-em Peptidementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the peptide vaccines derived from the amino acid sequence of antigens, peptide mimotopes, which are composed of amino acids different from those of native antigens, can mimic antigen-antibody binding sites structurally [57]. Active immunization with mimotopes would elicit antibodies against the corresponding epitopes.…”
Section: Introductionmentioning
confidence: 99%